Trends in cardiovascular care and event rates among First Nations and other people with diabetes in Ontario, Canada, 1996–2015 - Chu, Anna (CMAJ, 2019)
BACKGROUND: Rates of cardiovascular disease among people with diabetes have declined over the last 20–30 years. To determine whether First Nations people have experienced similar declines, we compared time trends in rates of cardiac event and disease management among First Nations people with diabetes and other people with diabetes in Ontario, Canada. METHODS: We conducted a retrospective cohort study of patients aged 20 to 105 years with diabetes between 1996 and 2015, using linked health administrative databases. Outcomes compared were the annual incidence of each admission to hospital for myocardial infarction and heart failure, and death owing to ischemic heart disease. Management indicators were coronary revascularization and prescription rates for cardioprotective medications. Overall rates and annual percent changes were compared using Poisson regression. RESULTS: Incidence rates for all cardiac outcomes decreased over the study period. The greatest relative annual decline among First Nations men and women were observed in ischemic heart disease death (4.4%, 95% confidence interval [CI] 3.0 to 5.9) and heart failure (5.4%, 95% CI 4.5 to 6.4), respectively. Among other men and women, the greatest annual declines were seen in ischemic heart disease death (6.3%, 95% CI 6.1 to 6.5 and 7.3%, 95% CI 7.1 to 7.6, respectively). However, all absolute cardiac event rates were higher among First Nations people (p < 0.001). Coronary artery revascularization procedures and prescriptions for cardioprotective medications increased among First Nations people, while only prescriptions increased among other people. INTERPRETATION: Over the last 20 years, the incidence of cardiac events has declined among First Nations people with diabetes, but remains higher than other people with diabetes in Ontario. For continued reductions in incidence, future efforts need to recognize First Nations people’s unique social and cultural determinants of health.